Peningkatan Keterampilan Menulis Berita dengan Pendekatan Terpadu dan Media Gambar pada Siswa Kelas VIII SMP Negeri 1 Teras - Hartati, Sri (Muhammadiyah University Press, 2015)
The purpose of the research is to increase news-writing skills by applying integrated approach and images utilization.The research is a type of action research which was conducted in 3 cycles. The main activities of the research were done in 4 steps: action planning, action implementation, observation, and reflection. The research was conducted to classVIIIA on the second term year 2013/2014 of Negeri 1 Teras Junior High School located in Boyolali. The subjects particularly were members of class VIIIA, consisting 32 students in total with the same ratio of girls and boys. The research uses field notes, observation guidelines, and news-writing trials as a method of collecting data. Descriptive-Qualitative method is used to analyse the development of writing skills. Both the process and the final results are analysed for this research. There are three conducted cycles. The result of the research showed that integrated approach and imagesutilization successfully increase the news-writing skills of the students both quantitatively and qualitatively. Initially, merely 7 of 32 students or approximately 21.88% of the students pass the average level while the classical learning mastering is 70.83%. After the first cycle has been done, the number of students who pass the average level increased significantly to 26 out of 32 or 81.25% while classical learning mastery increases to 77.89%. As a result, the succeed criteria of the research has not been achieved yet. The mean score of the students on first cycle is 77.89. Classical learning mastery is 85.07% therefore the succeed criteria has been passed this time. The mean score of the students on the second cycle is 85.07 which increases significantly compared to that on the first cycle.